The impact of economic policy uncertainty and oil market uncertainty on Malaysian stock market returns: a comparison between EPU in the United States and China - Cheong, Ying Ying; Lim, Yiwei; Loo, Xiang Ni; Tan, Valerie Zi Xuan; Yeap, Zi Wei (2019)
This research project examines the relationship between Economic Policy Uncertainty (EPU), oil market uncertainty on Malaysian stock market return. Particularly, there is a comparison between the impact of EPU in the US and EPU in China on Malaysian stock market return. Time series data is applied on this research, which the data is collected on monthly basis, starting from May 2007 to December 2018. The research data has gone through various tests such as Augmented Dickey Fuller (ADF) test, Phillip Perron (PP) test, Bound test, Autoregressive Conditional Heteroskedasticity (ARCH) test, Breusch-Godfrey Serial Correlation LM test and Ramsey RESET test in order to determine the validity of the regression model. Hence, the regression model has proven to free from unit root, heteroscedasticity, autocorrelation and specification error problem. The employment of Autoregressive Distributive Lag (ARDL) in this study aims to examine the existence of a long run relationship between dependent and independent variables. The outcome shows that there is a long-run equilibrium relationship between EPU, oil market uncertainty and Malaysian stock market return. Moreover, the findings of this research indicate that all independent variables including EPU in the US, EPU in China and oil market uncertainty have negative impact on Malaysian stock market return. In brief, these results bring significant implication to investors, policymakers and future researchers.